Institutional bidding behaviors during IPO bookbuilding: Evidence from Korea - Eom, Chanyoung (Journal of Corporate Finance, 2018)
Using a unique Korean initial public offering bookbuilding dataset, this study examines the impacts of presales to institutions and premarket interest on institutional bidding decisions, and makes the following observations. First, there is no significant relationship between presales and bidding decisions. This can be attributed to the fact that Korean underwriters offer institutions more allocations of less underpriced shares. Second, institutions become more willing to bid aggressively as premarket interest increases. Third, institutional incentive to submit aggressive bids is positively related to underwriter pricing discretion. Fourth, bidding strategies are conditional on the different degrees of pricing discretion. Overall, this study's evidence concludes the endogeneity of institutional bidding decisions in premarket auctions.